Algorithmic Morality and Local Value Anchors: How ABS–SBK Mediates Digital Populism in Indonesia’s Regional Politics - Lestari, Yayuk; Rinaldi; Okditazeini, Vannyora (Ilomata International Journal of Social Science, 2026)
This study explores the intersection between social media discourse in West Sumatra and formal governmental processes, focusing on the cultural idiom Adat Basandi Syarak, Syarak Basandi Kitabullah (ABS–SBK). This Minangkabau moral framework is analyzed as a highly "amplifiable" tool within algorithmic media environments. Utilizing digital discourse analysis and online trace mapping, the research examines how moral emotions expressed online are magnified by media gatekeeping and subsequently integrated into formal policy deliberations. Theoretically, the study introduces "local-value-anchored digital populism" to explain how localized idioms become institutionally actionable within Indonesia’s regional politics. Data sources include social media content from key figures, user interactions, news reports, and official documents. The findings reveal a recurring affective-institutional pattern: digital emotions are amplified by news media and then translated by local authorities and customary institutions into formal regulations or initiatives. This dynamic emerges from the convergence of three forces: public emotions, social media algorithms, and institutional structures. When used as a moral frame, the ABS–SBK idiom bridges public affective responses with state procedures, transforming local values into policy language and sources of political legitimacy. Consequently, digital populism in West Sumatra serves as a form of symbolic power construction. It reconfigures the relationship between religion, customary authority, and the state within the digital public sphere, moving beyond mere value-based communication to influence formal institutional channels like bylaws and customary councils.